THE EFFECTIVENESS OF THE DRUG DIPROCARB FOR BABESIOSIS IN CARNIVORES FROM MOSCOW AND THE MOSCOW REGION - E. S. Belomyttseva; R. T. Safiullin (Российский паразитологический журнал, 2019)
Objective of research: The purpose of this study was to investigate the efficacy of the drug Diprocarb with the main active ingredient Imidocarb Propionate. One milliliter (mL) of Diprocarb contains 120 mg of Imidocarb Dipropionate. Material and methods: Research was conducted in Moscow and the Moscow region (Ramensky and Podolsky districts) using an example of spontaneous infestation of dogs with babesiosis. The studies were carried out at veterinary clinics using laboratory studies of the blood of infected animals, as well as the study of ixodid ticks, that are the main vectors of Babesia canis. Monitoring of physical status of animals was being performed from the moment of infestation with babesiosis to the complete disappearance of parasites from the blood as well as the products of their vital activity. Diprocarb was used as the main drug and the symptomatic therapy was conducted. Results and discussion: The drug showed 100% effectiveness when applied at a dose of 6 mg per kg of animal weight. Diprocarb has been proven to be highly effective for the treatment of parasitic blood diseases transmitted by ixodid ticks.